2023
DOI: 10.3390/ijms24086886
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of PRE Genes in Moso Bamboo (Phyllostachys edulis)

Abstract: Basic helix–loop–helix (bHLH)/HLH transcription factors are involved in various aspects of the growth and development of plants. Here, we identified four HLH genes, PePRE1-4, in moso bamboo plants that are homologous to Arabidopsis PRE genes. In bamboo seedlings, PePRE1/3 were found to be highly expressed in the internode and lamina joint by using quantitative RT-PCR analysis. In the elongating internode of bamboo shoots, PePRE genes are expressed at higher levels in the basal segment than in the mature top se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The members, including AtbHLH68, AtbHLH006 and AtbHLH122, have been verified to mediate drought‐induced stress responses in Arabidopsis (Abe et al, 2003; Le Hir et al, 2017; Liu et al, 2014). A recent study revealed that PePREs may regulate bamboo shoot growth via multiple signalling pathways (Zheng et al, 2023). However, the molecular mechanisms of bHLH involved in the stress response of moso bamboo remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The members, including AtbHLH68, AtbHLH006 and AtbHLH122, have been verified to mediate drought‐induced stress responses in Arabidopsis (Abe et al, 2003; Le Hir et al, 2017; Liu et al, 2014). A recent study revealed that PePREs may regulate bamboo shoot growth via multiple signalling pathways (Zheng et al, 2023). However, the molecular mechanisms of bHLH involved in the stress response of moso bamboo remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%